Zen and the Art of Transdisciplinary Postgraduate Studies : Final Report. - Mitchell, Cynthia (Australian Learning and Teaching Council (ALTC), 2009)
Final report from a project focused on developing appropriate evaluation quality criteria for transdisciplinary/interdisciplinary doctoral research for use by students, supervisors and others. The goal was to provide a frame that is consistent across different discipline areas, as different disciplines judge quality in different ways, but specifically addressing implications for transdisciplinary/ interdisciplinary research.